Participation of Colleges of Business Administration in Saudi Universities in Achieving Sustainable Development for Saudi Society: Focus on College of Business Administration at TU (The International Journal for Scientific Research, 2023)
The aim of this research is to know the participation of business administration colleges in Saudi universities in achieving sustainable development for the Saudi society, with their participation in the goals of sustainable development and sustainability, by reviewing the participation of these colleges in community service and achieving its development and progress and assessing the extent of their contribution to achieving the well-being of this Saudi society. Highlighting the most important gains that can be achieved for the community in light of the participation of these colleges in providing services and the participation of sustainable development goals for society, and trying to know the future plans of these colleges in this field, while giving a clear and comprehensive idea of the development taking place in them, and what these colleges contain of Modern techniques and methods that can be used to achieve many advantages and gains for the Gulf and Saudi society in particular, and to identify the most important problems and obstacles facing these colleges in their participation in achieving the required development and well-being for the Saudi society, all by focusing on the College of Business Administration at Taif University, the place of study, to work on Provide appropriate solutions.
Keywords: Colleges; Business Administration; Community; Development; Sustainable